2017
DOI: 10.1038/onc.2017.356
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1-repressed microRNAs inhibit autocrine signaling that promotes vascular mimicry of breast cancer cells

Abstract: During normal tumor growth and in response to some therapies, tumor cells experience acute or chronic deprivation of nutrients and oxygen and induce tumor vascularization. While this occurs predominately through sprouting angiogenesis, tumor cells have also been shown to directly contribute to vessel formation through vascular mimicry (VM) and/or endothelial transdifferentiation. The extrinsic and intrinsic mechanisms underlying tumor cell adoption of endothelial phenotypes, however, are not well understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 63 publications
1
33
0
1
Order By: Relevance
“…also reported that ZEB1 is expressed in both tumor and stromal cells of the breast (40). ZEB1 directly increases the expression of proinflammatory cytokines such as IL6 and IL8, and it promotes vascular mimicry of breast cancer cells by remodeling extracellular matrix (33,41). We had previously demonstrated that cytokines such as TNF induce the expression of ZEB1 (42).…”
Section: Discussionmentioning
confidence: 93%
“…also reported that ZEB1 is expressed in both tumor and stromal cells of the breast (40). ZEB1 directly increases the expression of proinflammatory cytokines such as IL6 and IL8, and it promotes vascular mimicry of breast cancer cells by remodeling extracellular matrix (33,41). We had previously demonstrated that cytokines such as TNF induce the expression of ZEB1 (42).…”
Section: Discussionmentioning
confidence: 93%
“…During this process, the secreted proteins fibronectin 1 (FN1) and serine protease inhibitor family E member 2 (SERPINE2) are essential for vascular mimicry (VM) in this system. These secreted factors were upregulated in mesenchymal cells by ZEB1-repressed miRNA clusters, promoting autocrine signaling, which was followed by increased VM in breast cancer cells [80]. In clinical studies, ZEB1 was found to be significantly associated with the depth of invasion, lymph node metastasis and TNM stage in digestive cancer patients, as well as in patients with breast cancer [81].…”
Section: Tumor Growth Metastasis and Emtmentioning
confidence: 99%
“…Low-density lipoprotein receptor-related protein 1 (LRP1) and ITGB1 are receptors for these secreted proteins. Evidence shows that miR-183 regulates those autocrine signal and VM formation [51]. In addition, hypoxia-induced transcription factors (HIFs) are upregulated before angiogenesis due to hypoxia.…”
Section: Roles Of Mir-183 In Microangiogenesismentioning
confidence: 99%